Rytų baltų CiR tipo veiksmažodžiai - Pakalniškienė, Dalia (Baltistica, 2005)
EASTERN BALTIC CiR TYPE VERBS This article analyzes CiR type verbs in the Eastern Baltic languages and attempts to explain their origin and evolution. The criterion for inclusion as a subject for investigation – the root structure – allows for the discovery of general patterns in the history of verbs of the given structural type and the development of these verbs in the separate Baltic languages, and can provide a better definition of archaic features and innovations, because the root structure is closely related to the morphological structure and categorial semantics (especially in the Lithuanian language). According to various sources, there are approximately 30 CiR type verbs common to the Eastern Baltic languages (there are more in the Lithuanian language). In regard to morphological structure these are rather varied: a-stem, ia-stem, infix and sta-stem (the morphological structure also depends on the root final element: Cin are a-stem, Cir, Cil ia-stem or sto-stem, Cim are sta-stem). l. The largest group consists of infix and sta-stem verbs (15). 1.1. The majority of these form diathetic pairs with ia-stem verbs (10). The categorial semantics of infix and sta-stem verbs – the mutative meaning – is opposed to the causative meaning of ia-stem verbs, e.g. Lith. bẽria / bỹra : Latv. ber̦u / bir̃stu. This opposition has not been documented in the Old Prussian language. 1.2. Several of the verbs preserve Indo-European roots (5), but differ in morphological structure, these being infix and sta-stems or crossovers from a-stems, e.g.: Lith. mìršta : Latv. mir̃stu, Lith. gìmsta // gẽma : Latv. dzìmstu // dzemu. 2. Only half as many ia-stem CiR type verbs have been discovered (7), e.g. Lith. skìria – skýrė : Latv. šķir̦u – šķîru. 3. Eight Eastern Baltic a-stem verbs have CiR type roots. 3.1. Mostly a-stem verbs with quantitative vowel changes were identified (6). In the Latvian language the preterite may occur without vowel lengthening; moreover, some of the Latvian verbs have parallel ia-stem forms in the dialects. All express active action, cf. Lith. trìna – trýnė : Latvian trinu // trin̦u – trinu // trînu ‘to sharpen or grind (a blade), to rub or grate’ : OPr. trinie. 3.2. Two of the a-stem verbs have qualitative vowel gradation (there are more vestigial apophonic paradigms in the dialects): Lith. vérda // vìra // vera – vìrė : Latv. vę̂rd – vira, Lith. gẽna – gìnė : Latv. dzęnu – dzinu. These several archaic paradigms are at the early stage, from which new structural models began to develop in the Eastern Baltic languages. The dialect present tense base forms of the Eastern Baltic languages demonstrate that this type was much more plentiful previously, cf. Lith. dẽla – dìlo, Latv. dęl; Lith. svẽla; Latv. svęl; Lith. gẽma, Latv. dzęmu. These bear witness to former paradigms with qualitative vowel gradation; later in both of the Baltic languages the vocalism was generalized for the entire paradigm. Multiple lines of development can be seen: 1) most frequently the appearance of binary oppositions: Lith. kẽlia / kỹla // kìlsta : Latv. ceļu / cilstu – diathetic opposition with differentiated categorial semantics, morphological structure and vocalism; 2) more rarely ternary oppositions develop: Lith. skẽlia I skìlia / skỹla : Latv. šķeļu / šķiļu; 3) zero-grade roots are generalized and acquire either a, ia-stem or infix or sta-stem structure, depending on the categorial semantics (and the root-final sonant), cf. Lith. trìna – trýnė : Latv. trinu // trin̦u – trinu // trînu ‘to sharpen or grind (a blade), to rub or grate’; Lith. gìria – gýrė : Latv. dzir̦u – dzĩru or Lith. gìmsta – gìmė, Latv. dzìmstu – dzimu. Thus new structural models of the Eastern Baltic verbs developed. Evolution, origin. 1. The processes discussed should be considered an Eastern Baltic innovation, because the Old Prussian language doesn’t show this sort of differentiation of lexemes. The Baltic inheritance is not great, just a few verbs common to all the Baltic languages. The interpretation of Old Prussian vocalism is very often problematic – root vowel gradation can be perceived or not – but it’s probable that verbal oppositions with differentiated vocalism, morphological structure and categorial semantics did not occur, compare OPr. lemlai – limāts ‘broke’, which might have had vowel gradation. Moreover, there are further differences between the verbs of the three Baltic languages and between the Eastern Baltic languages, cf. the recently created Lith. gìna – gýnė with another kind of root in OPr. guntwei, gunnimai, Latv. dzęnu – dzinu. The innovations in the different languages are obvious. In this regard the expansion of the causativa / resultativa opposition in Lithuanian is distinctive, e.g. gẽria / gìrsta, svẽria / svỹra, and pairs differentiating the limits of action have also been created, such as gẽlia / gýla, vẽmia / -vìmsta. 2. Baltic verbs usually preserve Indo-European CeR-/CR̥- type roots, from which verbs denoting oppositions developed in the Eastern Baltic languages, or the zero-grade was generalized. Correspondences in the Indo-European languages are varied in terms of morphology, vocalism and semantics. There are various transformations in the different languages or branches: one set of languages develops to a great degree inflectional vowel gradation or modifies it in individual ways, while another set of languages generalizes one or another vowel grade. In any case, it is clear that apophonic lexemes were not differentiated, i.e. vowel gradation was not used to create separate lexemes. Thus the apophonic verbal paradigms of the Eastern Baits have been remodeled in an original way, by an intimate linking of morphology, root structure and categorial semantics.